SOSIALISASI PENERAPAN GOOD GOVERNANCE DALAM UPAYA MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI DESA PAKUNCEN KABUPATEN SERANG - Alwajir, Dede Qodrat; Rachman, Arief; Prahima, Parko; Hartoko, Gatot; Bangsawan, Try Adhi; Atomy, Sri; Amilia, Rizki; Saepudin, Eli Apud (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Pakuncen Village, Bojonegara Subdistrict, Serang Regency, still faces various problems in the delivery of public services, such as a lack of transparency, accountability and community participation. This results in the low quality of public services received by the community. This study aims to determine the effectiveness of socialization of good governance implementation in an effort to improve the quality of public services in Pakuncen Village. The research method used is qualitative research with a case study approach. Data collection techniques were conducted through observation, interviews, and documentation. The results showed that the socialization of good governance implementation in Pakuncen Village has not been fully effective in improving the quality of public services. This is caused by several factors, such as the lack of public understanding of good governance, the lack of facilities and infrastructure that support the implementation of good governance, and the unoptimal role of village officials in implementing good governance.